Democracy's Body : Judson Dance Theatre, 1962-1964 - Banes, Sally (Book collections on Project MUSE., 1993)
Judson Dance Theater involved such collaborators as Merce Cunningham, Yvonne Rainer, Steve Paxton, Carolee Schneemann, Trisha Brown, Robert Rauschenberg, David Tudor, et al.